Parents’ satisfaction on children’s dental care received at the Kulliyyah of Dentistry, International Islamic University Malaysia. - Harun, Nor Asilah; Abu Kassim, Noor Lide; Muhannad Kashmoola, Sayfaldeen; Ghazali, Ahmad Badruddin (Intenational Islamic University Malaysia, 2018)
Introduction: Part of the undergraduate training in dental school is treating dental patients under close supervision of trained supervisors. Islam emphasises the highest quality in service rendered. Aim: To evaluate parent’s satisfaction with their children’s dental care provided by undergraduate dental students at the Student Polyclinic, Kulliyyah of Dentistry (KOD), International Islamic University Malaysia (IIUM). Materials and Methodology: This is a cross-sectional descriptive study. A self-administered questionnaire with questions on accessibility and availability, physical environment, service quality, interpersonal communication, cost of treatment, efficacy and treatment outcome was distributed to parents whose children received dental treatment anytime January 2013 to October 2013. Data collected was analysed using the Independent Sample T-Test, and Mann-Whitney Test. Results: 70 questionnaires were completed and analysed. The results showed that the average level of parental satisfaction was high. The parents were most satisfied with students’ interpersonal communication. The level of satisfaction of parents of female children is higher than parents of male children although the difference was not significant. No significant differences were found in relation to which parent accompanied the child for treatment and the parent’s education level. However, the parent’s level of satisfaction is associated with type of occupation, where non-health-related workers expressed higher level of satisfaction (p < 0.05). Conclusion: Parents were generally satisfied with the care that their children received, mainly with the aspect of students’ interpersonal communication and physical environment of the clinic. The results also indicated that level of satisfaction is associated with the nature of the parent’s occupation.